Environmental literacy of youth movement members – is environmentalism a component of their social activism?. Issue 4 (21st April 2017) - Goldman, Daphne; Pe'er, Sara; Yavetz, Bela
Abstract : Youth-movements in Israel are non-formal organizations that educate for social and political involvement and provide a broad platform for youth involvement in the community. This study explored the question: does the social activism of adolescents who both elect for membership in youth movements and a leadership role of instructing younger members also reflect itself in environmentalism? In a survey of 1496 young instructors drawn from 15 official youth movements, findings on environmental literacy variables show youth are only generally knowledgeable about environmental problems; express 'technical-optimism' which leads them to limited concern for the environment; show limited recognition of the importance of environmental education, and show limited acknowledgment of the necessity for changes in personal consumerism. Findings also show that environmental issues are not on their mind since they are not a conversation topic with peers or family. Nonetheless, these youth also demonstrate strong self-efficacy to effect change; view themselves as role models for younger members; and express willingness to include environmentally-supportive activities within regular youth movement activities. Their valuing of nature also provides a foundation for building other environmental values. Further analysis shows how these findings can contribute theoretical and practical tools for incorporating sustainability within the youth movement framework, and help realize their potential for promoting sustainability in society.